বাংলাদেশের ভূমিরাজস্ব ব্যবস্থা : (প্রাচীন যুগ থেকে ১৭৬৩ খ্রিস্টাব্দ পর্যন্ত) প্রথম খন্ড - ইসলাম, কাবেদুল. 1964- (ঢাকা : মাওলা ব্রাদার্স, 2001)
History of the land revenue system of Bangladesh from ancient times to 1763.
Includes bibliographical references (v. 1, p. 416-453).
In Bengali; includes passages in English.
Keywords: Land tenure -- Bangladesh -- History; Land tenure